Den dybtgående orden, der kaldes turbulens: Dramaturgiens tre ansigter - Barba, Eugenio; Skeel, Ulrik (Peripeti, 2007)
In this essay on the three faces of dramaturgy, Eugenio Barba reflects on his theatrical works.